4w+19=-7(w-9)

Simple and best practice solution for 4w+19=-7(w-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w+19=-7(w-9) equation:


Simplifying
4w + 19 = -7(w + -9)

Reorder the terms:
19 + 4w = -7(w + -9)

Reorder the terms:
19 + 4w = -7(-9 + w)
19 + 4w = (-9 * -7 + w * -7)
19 + 4w = (63 + -7w)

Solving
19 + 4w = 63 + -7w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '7w' to each side of the equation.
19 + 4w + 7w = 63 + -7w + 7w

Combine like terms: 4w + 7w = 11w
19 + 11w = 63 + -7w + 7w

Combine like terms: -7w + 7w = 0
19 + 11w = 63 + 0
19 + 11w = 63

Add '-19' to each side of the equation.
19 + -19 + 11w = 63 + -19

Combine like terms: 19 + -19 = 0
0 + 11w = 63 + -19
11w = 63 + -19

Combine like terms: 63 + -19 = 44
11w = 44

Divide each side by '11'.
w = 4

Simplifying
w = 4

See similar equations:

| X-6-25x^(1/2) | | 7+x+1=6x | | -14+26=-2(x+5) | | 7x-8(2x-3)=2(3x-9)-5x | | -10y+3y= | | 39+8p=-3(-5p-6) | | V=3.14525 | | 8+4=2(7-1) | | 4x+44=x+17 | | 8+4=2(5-1) | | 4x+3-(x-5)=3x-(5x+6) | | -3x-12x=175 | | X=717.2+-1x | | X+(x+3.4)=720.6 | | 4x-8=4(x-7) | | y=log(3x^2+5x-2) | | 40x+5(1.5x)=900 | | 4(2x-3)+5(X-1)=23 | | 30-20+20x=10 | | X+(x+7.8)=726.2 | | n-38=50 | | 8+2*(-8)-6= | | -17+5=-4(x+1) | | x+22=3x+6 | | x^2/ | | 8(2c+4)=0 | | 84=4v-2(X-3)-3x | | 160+170+400+x=1000 | | 128=2n+8(n+6v) | | 5/9d=9/4 | | 11x+3=10x+3 | | (3/7)x-1=(2/3)(6x-2) |

Equations solver categories